Effect of some fungicides on seed mycoflora, germination, viability and their persistence in treated seeds (The Journal of Plant Protection Sciences, 2020)
The effect of some fungicides on seed mycoflora, germination, seed viability, and their persistence in treated seeds of mungbean, mustard, and rice was studied in vitro. The highest appearance of pathogens, namely Alternaria alternata, was recorded in seeds of mungbean (Phaseolus aureus Roxb.), A. brassicae in mustard (Brassica campestris L.), and Drechslera oryzae in rice (Oryza sativa L.). Propineb 70WP and prochloraz 45EC considerably reduced the appearance of A. alternata, and flusilazole 40EC reduced Fusarium sp. in mungbean seed compared to the untreated control.
Keywords: Fungicides; mustard; mungbean; rice; seed mycoflora; seed germination; viability; persistence